2016
DOI: 10.1242/dev.136127
|View full text |Cite
|
Sign up to set email alerts
|

Integration of actomyosin contractility with cell-cell adhesion during dorsal closure

Abstract: In this work, we combine genetic perturbation, time-lapse imaging and quantitative image analysis to investigate how pulsatile actomyosin contractility drives cell oscillations, apical cell contraction and tissue closure during morphogenesis of the amnioserosa, the main force-generating tissue during the dorsal closure in Drosophila. We show that Myosin activity determines the oscillatory and contractile behaviour of amnioserosa cells. Reducing Myosin activity prevents cell shape oscillations and reduces cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
(67 reference statements)
1
31
0
1
Order By: Relevance
“…, 2011; Levayer and Lecuit, 2013; Duque and Gorfinkiel, 2016). We therefore investigated cadherin-mediated adhesion in mys −/− mutants (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…, 2011; Levayer and Lecuit, 2013; Duque and Gorfinkiel, 2016). We therefore investigated cadherin-mediated adhesion in mys −/− mutants (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The amnioserosa, an extra-embryonic tissue, covers the dorsal hole and contributes to ectodermal closure by providing contractile forces that pull the contralateral ectodermal sheets together [54, 57, 58]. DC requires DE-Cad-mediated adhesion for ectodermal migration and fusion [59, 60]. To analyze Raskol and DE-Cad dynamics, we conducted time-lapse live imaging of embryos expressing YFP-tagged Raskol and RFP-tagged DE-Cad during DC.…”
Section: Resultsmentioning
confidence: 99%
“…Here, Raskol colocalized with actin suggesting that it may play a role in actin dynamics. Since Raskol contains a GAP domain and colocalizes with the cortical actin cytoskeleton in BCs, the FE, the amnioserosa and the dorsal most ectodermal cells [55, 60], we sought to determine whether it functions to regulate actin organization in BCs. We stained egg chambers expressing raskol RNAi in the BCs under the control of slbo -GAL4 driver for F-actin (phalloidin) and nuclei (DAPI) to assess F-actin distribution in the migrating cluster.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the myosin activity in amnioserosa cells increases as dorsal closure proceeds (35), implying an enhanced amnioserosa contraction due to the increase in myosin activation coefficient α in Eq. 2 (38). To account for this biochemical feature, we gradually increase α while keeping the myosin deactivation rate β fixed.…”
Section: Resultsmentioning
confidence: 99%